Friction forces determine cytoplasmic reorganization and shape changes of ascidian oocytes upon fertilization - Caballero Mancebo, Silvia; Shinde, Rushikesh; Bolger-Munro, Madison; Peruzzo, Matilda; Szep, Gregory; Steccari, Irene; Labrousse Arias, David; Zheden, Vanessa; Merrin, Jack; Callan-Jones, Andrew; Voituriez, Raphaël; Heisenberg, Carl-Philipp J (Nature Physics)
Contraction and flow of the actin cell cortex have emerged as a common principle by which cells reorganize their cytoplasm and take shape. However, how these cortical flows interact with adjacent cytoplasmic components, changing their form and localization, and how this affects cytoplasmic organization and cell shape remains unclear. Here we show that in ascidian oocytes, the cooperative activities of cortical actomyosin flows and deformation of the adjacent mitochondria-rich myoplasm drive oocyte cytoplasmic reorganization and shape changes following fertilization. We show that vegetal-directed cortical actomyosin flows, established upon oocyte fertilization, lead to both the accumulation of cortical actin at the vegetal pole of the zygote and compression and local buckling of the adjacent elastic solid-like myoplasm layer due to friction forces generated at their interface. Once cortical flows have ceased, the multiple myoplasm buckles resolve into one larger buckle, which again drives the formation of the contraction pole—a protuberance of the zygote’s vegetal pole where maternal mRNAs accumulate. Thus, our findings reveal a mechanism where cortical actomyosin network flows determine cytoplasmic reorganization and cell shape by deforming adjacent cytoplasmic components through friction forces.

Combined effect of cell geometry and polarity domains determines the orientation of unequal division - Godard, Benoit G; Dumollard, Remi; Heisenberg, Carl-Philipp J; Mcdougall, Alex (eLife)
Cell division orientation is thought to result from a competition between cell geometry and polarity domains controlling the position of the mitotic spindle during mitosis. Depending on the level of cell shape anisotropy or the strength of the polarity domain, one dominates the other and determines the orientation of the spindle. Whether and how such competition is also at work to determine unequal cell division (UCD), producing daughter cells of different size, remains unclear. Here, we show that cell geometry and polarity domains cooperate, rather than compete, in positioning the cleavage plane during UCDs in early ascidian embryos. We found that the UCDs and their orientation at the ascidian third cleavage rely on the spindle tilting in an anisotropic cell shape, and cortical polarity domains exerting different effects on spindle astral microtubules. By systematically varying mitotic cell shape, we could modulate the effect of attractive and repulsive polarity domains and consequently generate predicted daughter cell size asymmetries and position. We therefore propose that the spindle position during UCD is set by the combined activities of cell geometry and polarity domains, where cell geometry modulates the effect of cortical polarity domain(s).

Zebrafish gastrulation: Putting fate in motion - Nunes Pinheiro, Diana C; Heisenberg, Carl-Philipp J (Gastrulation: From Embryonic Pattern to Form)
Gastrulation entails specification and formation of three embryonic germ layers—ectoderm, mesoderm and endoderm—thereby establishing the basis for the future body plan. In zebrafish embryos, germ layer specification occurs during blastula and early gastrula stages (Ho & Kimmel, 1993), a period when the main morphogenetic movements underlying gastrulation are initiated. Hence, the signals driving progenitor cell fate specification, such as Nodal ligands from the TGF-β family, also play key roles in regulating germ layer progenitor cell segregation (Carmany-Rampey & Schier, 2001; David & Rosa, 2001; Feldman et al., 2000; Gritsman et al., 1999; Keller et al., 2008). In this review, we summarize and discuss the main signaling pathways involved in germ layer progenitor cell fate specification and segregation, specifically focusing on recent advances in understanding the interplay between mesoderm and endoderm specification and the internalization movements at the onset of zebrafish gastrulation.